2016
DOI: 10.1057/palcomms.2016.7
|View full text |Cite
|
Sign up to set email alerts
|

What are male teachers’ understandings of masculinities?—an exploration of sex, gender and bodies in Irish primary schools

Abstract: Primary teaching has traditionally been framed by assumptions about gender. These commonly held, but seldom voiced, assumptions have a strong impact on male primary schoolteachers and on men considering teaching as a career. Focusing on the lives of five Irish male primary teachers, this article unpacks a number of the assumptions relating to men who teach children at primary level. Many of the assumptions are often shrouded in silence, which increases the difficulty in addressing them. In this context, discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…In this context, the discourse has constructed the relative under-representation of men as essentially unproblematic, with Martino and Rezai-Rashti (2012) arguing for a focus on the recruitment of good teachers, irrespective of their gender. While the gender equality lens has commonly and justifiably focused on women, and while many simplistic arguments calling for redressing the gender imbalance in teaching have rightly been refuted, a significant body of research has demonstrated that gender is of particular significance in the opportunities, experiences and expressions of being a teacher (O'Keeffe 2016;Skelton 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the discourse has constructed the relative under-representation of men as essentially unproblematic, with Martino and Rezai-Rashti (2012) arguing for a focus on the recruitment of good teachers, irrespective of their gender. While the gender equality lens has commonly and justifiably focused on women, and while many simplistic arguments calling for redressing the gender imbalance in teaching have rightly been refuted, a significant body of research has demonstrated that gender is of particular significance in the opportunities, experiences and expressions of being a teacher (O'Keeffe 2016;Skelton 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, schools can provide a more inclusive environment and atmosphere for male teachers. For example, male school teachers find the staffroom intimidating and lonely in a primary school in Ireland, according to interview findings (O'Keeffe, 2016). Therefore, the atmosphere for male teachers to work in primary schools needs to be improved to attract more male primary school teachers.…”
Section: Ways To Increase the Number Of Male Primary School Teachers ...mentioning
confidence: 99%
“…viziju institucije, izuzevši viziju koja je bliska kulturi brige 79 , što je dokaz da povijesni artefakti koji u sebi nose segregaciju i danas oblikuju obrazovni proces. Poučavanje djece i u javnoj sferi smatra se mekom opcijom 80 , a to je opcija žena odgovornih za djecu. Uvjerenje da je briga (kao izvrstan temelj za odgoj i nastavu) ženama prirođena te da im samim time ni poslovi odgoja i obrazovanja nisu teški, generira shvaćanje da žene taj posao mogu odraditi uz malu ili minimalnu naknadu.…”
Section: Familijarizacija Institucijskog Odgojno-obrazovnog Radaunclassified